Economic foundations of strategy - Mahoney, Joseph T. (Foundations for Organizational Science: A SAGE Publications Series, 2005)
Economic Foundations of Strategy provides not only the essential basic tenets of strategy, it also shows the inter-relationships of five major theories of the firm: the behavioral theory; transaction costs theory; property rights theory; agency theory; and dynamic resource-based theory.  Even though technological, organizational and institutional change advances breathlessly, the theories of the firm provided in this research book are durable principles that have stood, and the author maintains will continue to stand, the test of time.  Economic Foundations of Strategy emphasizes the complementarities among these five theories of organization, and the potential for integrating these theories in the evolving science of organization. Applications of these theories to business practice are emphasized throughout the book.